The Relationship Between Burnout Syndrome In Nurses In Psychiatric Clinics - Hasbi, Muhammad (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2024)
Nurses who work in the Psychiatric Clinic are also prone to burnout, where burnout is a problem caused by prolonged work pressure. There are several conditions that people experience burnout, namely emotional saturation, loss of motivation, and reduced commitment which results in a decrease in performance at work. This study is a correlative analytical study with a cross-sectional approach that analyzes the relationship between free and dependent variables using the Maslach-Trisni Burnout Inventory (M-TBI) instrument. The sample was taken by the Non-Probability consecutive sampling method. The study had 6 independent variables, and the sample size was determined based on the highest bivariate relationship. Data analysis was carried out by the Chi-Square test.   Pene; ITI found a relationship between gender (p = 0.001), age (p = 0.021), and job position (p = < 0.001) to burnout syndrome in nurses working in the Psychiatric Clinic. This study found a relationship of burnout syndrome in nurses who care for people with mental problems.